"Seroprevalence of Cytomegalovirus, Hepatitis B, Hepatitis C and Human Immunodeficiency Virus Antibodies among Volunteer Blood Donors " - R Moniri; Z Mosayebii; GA Mossavi (Tehran University of Medical Sciences, 2004)
The transfusion transmitted infections are potentially dangerous complications of transfusion therapy in immunocompromised patients. The aim of this study was to determine the prevalence of transmissible infections in blood donor population in Kashan, Iran. A total of 600 consecutive sera were tested for CMV-IgM antibody, HBsAg, hepatitis B core (HBc) antibody, hepatitis C (HCV) antibody, and HIV antibody with standard methods. Of the sera tested, 14 specimens (2.3%) were CMV-IgM positive. The frequency of seropositive revealed no significant differences between male and female donors. The frequency rates of CMV-IgM seropositive tests tend to decline with increasing the age. There was no relation between the frequency rates of CMV-IgM seropositive with the educational level, socioeconomic status, marital status, urban dweller and rural resident patients. The prevalence of HBV, HCV, and HIV antibody was 0.5%, 0.5%, and 0%, respectively. These findings implied important clinical applications because detection of CMV positive sera may reduce the risk for transmission of CMV in blood transfusion and thereby decrease the risk on CMV-induced complications.